The relationship between duration of infertility and intrauterine insemination: a multi-centers study - Allow, Ahmed Kaid Naji; Abdulmogny, A. Sadek S.M.; Bracamonte, Maryam; Mohammad, Wael (iMedPub Journals, 2016)
Abstract Introduction: The duration of infertility should be considered as a factor that may affect the outcome of Assisted Reproductive Techniques (ART). The aim of the present work is to examine the outcome of infertility treatment in relation to duration of infertility. Materials and methods: One hundred fifty-two couples with mild male infertility factor were involved in this retrospective study. Sixty nine couples from Allow In vitro Fertilization center (IVF), and remaining (83 couples) from Embryo Research and Infertility Treatment; Al-Nahrain University, Baghdad-Iraq. Intrauterine Insemination (IUI) had been done for all couples using the same ART. Results: The mean age of men was 35.88 ± 0.57 years and the duration of infertility was 5.44 ± 0.29 year (range=1-19 years). The higher pregnancy and life-birth rates was demonstrated in those couples suffering from infertility for duration less than 4 years in compare to those who had duration more than 10 years (P<0.003, r=-0.869). Abortion rate was observed in those couples who had duration more than 10 years in compare to those who have duration of infertility less than 4 years (P<0.0014). The linear life-birth rate, in both IVF centers, shows decrease by increase in the duration of infertility. Conclusion: The researchers conclude that by increase in the duration of infertility the outcome of assisted reproductive techniques -IUI will be decreased markedly. Keywords: Infertility; ART; IUI; Life birth rate